A Study on the Level of Usage of Personal Protective Equipment’s among the Building Construction Workers: A knowledge Domain (International Journal of Food and Nutritional Sciences, 2022)
Personal protective equipment (PPE) is equipment that will defend the workers against health and safety risks at work. Personal protective equipment or PPE is critical to keep workers in the workplace safely to do work. This study has been taken in and around of Mysuru city. The objectives of the study is to investigate about the knowledge and usage of Personnel Protective Equipment’s among the building construction workers in the study area. The Methods of the study is cross-sectional prospective in nature and 360 building construction workers have been selected for the purpose of the study by adopting stratified sampling techniques. As part of the study results it is found that the KMO value is 0.672 and it greater than.0.5, and The Chi-square test value is 690.749 and it is significant at one percent level. Together three components have explained 56.141 percent of variations. Conclusions: Personal protective equipment’s (PPE) PPE is equipment that will protect workers against health or safety risks on the job. The finding is to reduce worker exposure to dangers when engineering and administrative controls are not possible.